(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2023)
Sub-synchronous resonance (SSR) is a well-known phenomenon caused by power exchange between the network and the mechanical part of the generators. The STATCOM controller is a type of shunt FACTS devices employed to compensate the SSR and provide the necessary dynamics to the system. Investigating their contribution to the network requires a good representation of the STATCOM at different operating conditions. This paper presents two modelling techniques found in the literature, synchronous dq and dq-dynamic phasor modelling. The SSR frequency is included in the STATCOM model using a dq-dynamic phasor and compared with conventional dq modelling. The modelling is carried out for the small signal stability assessment techniques, while the validation is done using the time domain model under MATLAB/Simulink environment. In addition, the paper discusses the suitability of different stability measures to identify the stable operation of the STATCOM using the two derived models. The paper presented the suitability of criteria-based transfer functions to assess the SSR effect with the ability to track small signal changes.